2021
DOI: 10.4046/trd.2020.0063
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Death and BCG Vaccination Programs Worldwide

Abstract: Several clinical trials are being conducted worldwide to investigate the protective effect of the bacillus Calmette-Guérin (BCG) vaccine against death in healthcare providers who are working directly with coronavirus disease 2019 (COVID-19) patients. Clinical studies suggested that certain live vaccines, particularly the BCG vaccine, could reduce the mortality due to other diseases caused by non-targeted pathogens, most probably through the nonspecific effects (heterologous effects). By the end of May 2020, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…With the ongoing COVID-19 pandemic, there have been reports that patients who are BCG-vaccinated are less susceptible to serious illness and have less severe COVID-19 symptoms [82]. Several studies are currently being conducted worldwide to determine whether BCG vaccination has a protective effect against COVID-19 (clinicaltrials.gov#-NCT04537663, NCT04379336, NCT04369794, NCT04461379, NCT04347876) [82][83][84][85]. These studies indicate that the immunologic SNP panel could also be utilized as an important tool if BCG is preventative or can reduce the pathogenicity of COVID-19 as well as other infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing COVID-19 pandemic, there have been reports that patients who are BCG-vaccinated are less susceptible to serious illness and have less severe COVID-19 symptoms [82]. Several studies are currently being conducted worldwide to determine whether BCG vaccination has a protective effect against COVID-19 (clinicaltrials.gov#-NCT04537663, NCT04379336, NCT04369794, NCT04461379, NCT04347876) [82][83][84][85]. These studies indicate that the immunologic SNP panel could also be utilized as an important tool if BCG is preventative or can reduce the pathogenicity of COVID-19 as well as other infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The lethality reported by COVID-19 in countries with BCG vaccination is about 5.8 times lower than countries without the BCG vaccination program (159). Equivalent suggestions have been made by other studies supporting the notion of using the BCG vaccine to prevent severe COVID-19 at least in the most vulnerable groups, such as the elderly and healthcare personnel (160,161). Recently, a study in a hospital from the United Arab Emirates demonstrated that a boost with the BCG vaccine in the healthcare workers could reduce the disease caused by SARS-CoV-2 (162).…”
Section: Trained Immunity and Sars-cov-2 Infectionmentioning
confidence: 96%
“…Honorary professor, Dr DY Patil Univerity, Pune, India Email: wviroj@yahoo.com Dear Editor, I would like to share ideas on the publication "COVID-19 death and BCG vaccination programs worldwide. [1]". Jirjees et al concluded that "it can be concluded that the early establishment of BCG vaccination policy in any country is a key element in reducing the number of COVID-19 and tuberculosis death cases [1]."…”
mentioning
confidence: 99%
“…[1]". Jirjees et al concluded that "it can be concluded that the early establishment of BCG vaccination policy in any country is a key element in reducing the number of COVID-19 and tuberculosis death cases [1]." The interrelationship between COVID-19 and tuberculosis is interesting.…”
mentioning
confidence: 99%
See 1 more Smart Citation